KASIBA SEBAGAI SALAH SATU KEBIJAKAN PEMERINTAH DALAM PENYEOIAAN PERUMAHAAN' - Purwantiasning, Ari Widyati (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2016)
Abstract People growth and urbanization in urban area ha~' fmplied on increasing of housing need. The problem' 'araises, sin'ce the,·, housing supply islnwer than housing ,need, ' especfally', for,'middlelow ,'income people. The government had beeniliilialed todevelO~ ,corehc)usespoficy and offered housing development 'subsidies, fli'roiJghKPR' (Kredif Pemilikan Ramah) for middle low 'income peoplE;:' Based on t~ispolicy, smafland middle scale housings were ser)arcitediy built 'by both public and private developers, This situ3tionimplied 0/1 araising new problems since 1he housingdevelopmenlspreadly' squatted"ihurban areas. It impacts on un~integratedpI2n:ljng and high cost' of infrastructure maintenance. ltis important to promote a new approach to supply housing for middle low income peopl~ that more appropriate to urban integrated planning, named as KAS1BA (Kaw8san Slap Bangan). This paper aims to describeKASIBA in the term of goal managemem, involved <agents, and finance method. Keywords: KAS/BA, housing development, urban integrated planning